Association of salted tea (noon chai), Helicobacter pylori infection and gastric carcinoma - Illahi, Mir Fazil; Gani, Mubashir; Naqash, Sameer H.; Shah, Mubashir A. (International Surgery Journal, 2024)
Background: Gastric cancer remains the second leading cause of cancer-related deaths worldwide. Various dietary and environmental factors have been implicated in the pathogenesis of gastric cancer. Helicobacter pylori has strong association with peptic ulcer disease and gastric cancer. Methods: This study was conducted in department of general and minimal invasive surgery SKIMS Srinagar, from May 2019 to April 2022 comprising of 50 patients. All the patients were studied prospectively using set of questionnaires about the quantity and quality of salted tea. Final inferences were drawn after analysing the data using various statistical tools. Results: The most common age group was >60 years of age with male preponderance. Majority of patients had no comorbidity. About 50% of the patients were smokers. The most common histology found was intestinal type. 20% patients had proximal (cardia) tumor and 80% had distal location. Only 14% of the patients came positive for intra-operative H. pylori testing. Among the H. pylori positive patients, 14.3% were <40 years of age and 85.7% were >40 years of age. The most common histological grade found in H. pylori positive patients was poorly differentiated with signet ring cell type. About 88% of all the patients had a history of Noon chai intake with 14% positive and 86% negative for H. Pylori. Conclusions: There is a positive relation between Noon chai and gastric carcinoma and an inverse relation between ca stomach and presence of H. pylori intraoperatively at the time of surgical intervention.